UTILIZATION OF ORGANIC LIQUID WAS TEAS FERTILIZER WITH DIFFERENT CONCENTRATION ON THE GROWTH AND YIELD OF BOK CHOY (BRASSICA RAPA VAR. CHINENSIS) - Restu Dwi Nugroho; Muhammad Anshar Pasigai; Bahrudin Bahrudin (Tadulako University, 2017)
This research aimedto study the influence ofthe right type and concentration organic waste on the growth and yield of bok choy. This research was compiled using a randomized block design factorial with two treatment factors, The first factor type of waste, second factor of concentration spraying. Thus obtained 8 experimental unitsconsists oforganic liquid waste cow urine (concentration of 20%, 40%, 60% and 80%), organic liquid waste water catfish pond (concentration of 20%, 40%, 60% and 80%). Each unit treatment was repeated three times so that there were 24 experimental units. The observed variables includeplant height (cm), leaves number, fresh weight of roots stems and leaves (g), dry weight of roots, stems and leaves (g), the amount of leaf(cm2), and the fresh weight of the plants (ton ha-1). The results showed that interaction between the type of organic liquid waste concentration of 40% (equivalent to 40 mL L-1)gives better results than other concertation , Types of organic waste liquid cow urinegave better resultsthanorganic liquid waste water catfish pond, and the concentration better of organic liquid waste in a concentration of 40% (equivalent to 40 mL L-1).